2008
DOI: 10.1016/j.neuroscience.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of kappa opioid receptor gene in neuronal differentiation

Abstract: The gene of mouse kappa opioid receptor (KOR) utilizes two promoters, P1 and P2. P1 is active in various brain areas and constitutively in P19 mouse embryonal carcinoma cells. P2 is active in limited brain stem areas of adult animals and only in late differentiated cells of P19 induced for neuronal differentiation in the presence of nerve growth factor (NGF). NGF response of P2 was found to be mediated by a specific binding site for transcription factor activation protein 2 (AP2) located in P2. Electrophoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The current research, demonstrating the effects of stress on KOR epigenetic processes is in line with the indicated ability of external stimuli, including stressors such as forced swim exposure, to affect chromatin remodeling, DNA methylation, and histone modification of stress-associated genes and/or within stress-sensitive brain area (25). The change in c-Myc is most significant, which is consistent with studies of cell cultures (26)(27)(28). The increased acetylation of histone 4, reduced lysine dimethylation of histone 3, and reduced binding of HDAC1 are also consistent with changes on Pr1 chromatin in studying cultured cells where this promoter is found to be active (36).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current research, demonstrating the effects of stress on KOR epigenetic processes is in line with the indicated ability of external stimuli, including stressors such as forced swim exposure, to affect chromatin remodeling, DNA methylation, and histone modification of stress-associated genes and/or within stress-sensitive brain area (25). The change in c-Myc is most significant, which is consistent with studies of cell cultures (26)(27)(28). The increased acetylation of histone 4, reduced lysine dimethylation of histone 3, and reduced binding of HDAC1 are also consistent with changes on Pr1 chromatin in studying cultured cells where this promoter is found to be active (36).…”
Section: Discussionsupporting
confidence: 88%
“…Epigenetic regulation of the KOR gene in culture systems includes inputs like retinoic acid, nitric oxide and nerve growth factor (26)(27)(28)(29). However, whether and how the diverse promoter regions and PA sites of the KOR gene are subjected to differential epigenetic regulation in animals is unclear.…”
mentioning
confidence: 99%
“…Whether and how these effectors contribute specifically to EGF-stimulated neurite outgrowth needs to be evaluated in the future. Opioid receptors have been shown to be involved in neuronal differentiation (37)(38)(39). This study adds a functional role for KOR in the development of the nervous system, specifically in neurite/axon extension.…”
Section: Signal Of Egf To Stimulate Kor/dynorphin-dependent Axon Extementioning
confidence: 70%
“…Two recent studies found that H3K4 dimethylation, a marker of transcriptional activity, was enhanced in the promoter region of neuron-specific opioid receptors, whereas H3K9 trimethylation, a marker of transcriptional repression, was reduced (51,265). Another study found that the histone H3K27-specific histone demethylase JMJD3 is necessary for neural differentiation, as it demethylates H3K27, a modification indicating transcriptional repression, at the neuron-specific nestin promoter (38).…”
Section: Neural Differentiationmentioning
confidence: 99%